Optimal ordering quantity by retailer from supplier with transportation cost in a supply chain - Ndukum, Pascaline Liaken; Encho, Leo Tanyam; Soh , Mathurin; Okolo, Abraham (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
Successful retailer-supplier collaborative relationship enhance profitability in the delivery of products or services to customers in a supply and can help alleviate pressures along all key points in the supply system. A strong alliance can bring products to market faster; reduce production and logistics costs, drive market shares, and increase sales, while maximizing profit for both partners. The success of fast-moving consumer goods from the suppliers has a direct relationship with the performance of the leading retailers, which are their main channel of distribution. The objective of this study was to establish a profit model between a single supplier and multiple supply chain collaboration that will enhance response to customer requirements. We considered the costs for various parties and use a referenced simplified framework model to obtain joint optimal pair for the outcome of coordination between the retailer and supplier. Our results showed that the value of the annual cost, with the same optimal ordering quantity, is higher when the retailer incurs transportation cost than when the supplier incurs transportation cost. This study revealed that the supplier will minimize cost when incurring transportation charges and maximize profit.